O21 HIV testing in abortion services: missed opportunities for earlier diagnosis. (8th June 2017) - Logan, Louise; Folkard, Kate; Connor, Nicky; Ncube, Fortune; Nardone, Anthony
Abstract : Introduction: The 2016 National Institute of Clinical Excellence (NICE) HIV testing guidelines reiterated the need to include HIV testing in abortion services. This survey aimed to determine whether HIV testing was commissioned in abortion services and how much testing was performed. Methods: 143 CCGs were invited to provide service specifications and monitoring data for the number of women seen for care, tested for HIV and diagnosed as HIV positive. Results: Of 103 CCGs that responded, 45 (42%) stipulated that HIV testing should be offered to all women, 10 (9%) requested that providers work towards this, 27 (26%) requested sign-posting and 21 (20%) had no mention of HIV. All 10 CCGs in extremely high HIV prevalence areas (where diagnosed HIV is >5/1000) commissioned HIV testing. 54% (14/26) of CCGs in high prevalence areas (diagnosed HIV is 2–5/1000) and 45% (30/367) of CCGs in low prevalence areas (diagnosed HIV is <2/1000) did so. 40 of 103 CCGs reported testing data. Of 35, 023 women reported as seen for care, 35% (12, 179) were tested for HIV and 0.14% (17) tested positive. Uptake ranged from 0% to 97% and positivity ranged from 0% to 0.53%. Discussion: Overall positivity rates exceed those required to make HIV testing cost effective. Less than half the CCGs reported commissioning HIV testing in abortion services, including 54% in high prevalence areas. These gaps in service provision mean opportunities to diagnose women earlier; thereby improving their prognosis and reducing undiagnosed infection were missed. Further advocacy for testing HIV testing in abortion services is required.